An Analysis of the Impact of Cultural Knowledge on the Job Success of Managers in the General Department of Sports and Youth of Kerman Province - Salari Kiskani, Hamzeh; Solhjoo, Mohammad Hassan; Zareian, Hossein (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The primary aim of this study is to analyze the impact of cultural knowledge on the job success of sports managers. Methodology: The research is descriptive-correlational in nature. The statistical population included all managers of the General Department of Sports and Youth of Kerman Province (385 individuals) in 2022, with a sample size of 223 individuals (41 women and 182 men), selected using a random sampling method. The research instrument was a researcher-developed questionnaire, with a Cronbach’s alpha reliability coefficient of 0.89. Findings: The results indicated that all components of cultural knowledge had a positive and significant relationship with the job success of managers. The highest correlation was between supervision and control with job success (0.918), while the lowest correlation was between guidance and leadership with job success (0.352). Additionally, stepwise regression showed that all seven components could contribute to prediction, explaining 96.2% of the variance in the job success variable. Structural equation modeling also revealed a path coefficient of 0.975 and a t-value index of 412.62 between the two variables of cultural knowledge and job success. Conclusion: It appears that managers must have sufficient knowledge and awareness of the details of sports programs and their implementation. They should make accurate and low-error decisions in their job performance, and their planning should align with the organization’s objectives, aiming for its growth and development.